Understanding solid-state photoswitching in [Re(OMe2-bpy)(CO)3(η1-NO2)] crystals via in situ photocrystallography. Issue 39 (25th June 2018) - Hatcher, Lauren E.
Abstract : Single-crystal-to-single-crystal linkage isomerism is determined in a photoswitchable Re(i )-bpy crystal, shedding new light on the photoactive properties of potential Re(i )-photocatalysts. Abstract : Single-crystal-to-single-crystal nitro → nitrito isomerism is reported for the novel rhenium(i )-bipyridine complex [Re(OMe2 -bpy)(CO)3 (η 1 -NO2 )], achieving a maximum conversion of 66% to a photoinduced nitrito-(η 1 -O̲NO) isomer under continuous illumination. The 3D X-ray structure of the photoinduced isomer is determined by steady-state and psuedo-steady-state photocrystallographic methods, providing insight into the structural changes required to accommodate photoswitching. Photocrystallographic kinetic studies follow the progress of photoswitching with time, determining a reaction rate constant of k = 0.38(2) min −1 at 150 K. Linkage isomerism is fully-reversible on warming, and pseudo-steady-state experiments confirm that the photoexcited state is retained, at measurable occupancy, up to a temperature of 240 K. These results confirm the validity of combining photoactive linkage isomer and Re(i ) photocatalyst chemistries, and the detailed determination of the photoexcited state structure will facilitate the future design of new photoactive Re(i ) crystals for a range of applications.